Inflammatory infiltration into placentas of Neospora caninum challenged cattle correlates with clinical outcome of pregnancy - Canton, German Jose (2014)
Infection with Neospora caninum stimulates host cell-mediated immune responses, which may be responsible for placental damage leading to bovine abortion. The aim of this study was to compare immune responses in the bovine placenta, following experimental infection in different stages of pregnancy. Placentomes were examined by immunohistochemistry and inflammation in early gestation was generally moderate to severe, particularly in the placentas carrying non-viable foetuses, whereas it was milder in later stages, mainly characterised by the presence of CD3+, CD4+ and γδ T-cells. This distinctive cellular immune response may explain the milder clinical outcome observed when animals are infected in later gestation.